Rethinking cultural extinction: representation, identification and preservation - Nkeokelonye, Adaobi; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia Press, 2019)
Cultural extinction in our view is a collective term that is more representative of the threat to, and the extinction of all cultural forms. In providing an overview of the definitions, interdisciplinary uses, and causes of cultural extinction, our paper aims to contribute towards the strengthening of the tenuous discourse on the concept of cultural extinction. Through our review of literature, we find that available scholarship on causality commonly presents external forces that are exterior to the cultural group as responsible for triggering cultural extinction. Thus, there is need to expand research by looking into the role of the cultural groups themselves, being instrumental to the extinction of their tangible and intangible cultural heritage. Language as a form of culture has many standardized tools for assessing its status, but we have observed a comparative paucity of such tools for identifying the status of other cultural forms. To address this, we suggest the development of hybrid tools adapted from existing language status assessment tools. Finally, we recommend the need for more scholarship to advance the phenomena of cultural extinction as existing literatures are grossly inadequate. Future scholarship addressing the phenomena of cultural extinction could explore other cultural forms beyond language to offer balance to the discourse on the realities of cultural extinction.